Biaya Operasional Sepeda Motor Matic Dan Manual - Meidia Refiyanni; Muhammad Ikhsan (Universitas Teuku Umar, 2018)
This research was conducted to find out the comparison of operational cost of motorcycle between matic and manual. Determining adequate model for operational cost of two-wheeled motor vehicle, analyzing and identifying factors influencing operational cost of two-wheeled vehicles in Blang Puuk Village, Seunagan Sub-district. In this research, the statistical test, which includes correlation coefficient analysis, multiple linear regression, coefficient of determination (R2), T test and F test of dependent variable and independent variable. In performing statistical tests, data processing uses SPSS (Statistical Product and Service Solution) software version 23. Then after statistical tests continued by calculating the operational cost of vehicles based on type, capacity, and assembly year which includes fixed cost and cost variable (variable cost). The result of the research shows that the analysis model of Vehicle Operating Cost (BOK) of two wheel in Blang Puuk Village is Y = 11,167 + 0,004X1 + 0,001X2 + 0,000X3 + 0,002X4 - 0,003X5 + 0,001X¬6 + 0,001X7 + 3,905X8. The most dominant factor influences travel in this case the operational cost is the use of fuel. Maximum Vehicle Operational Cost (BOK) for every 1 km of travel: vehicles with capacity of 100 CC (duck type) of 2004-2009 assembly year which is Rp. 865.75; capacity of 125 CC (duck type) of assembly year 2004-2009 and 2010-2015 amounting to Rp. 674,78 and 605,57; capacity 110 CC (scooter matic type) assembly year 2004-2009 and 2010-2015 that is equal to Rp. 570,88 and Rp. 995,05; capacity 115 CC (scooter matic type) assembly year 2004-2009 and 2010-2015 that amounted to Rp. 629, 60 and Rp. 762, 96. Keywords: Modeling, BOK, Vehicle, SPSS